Investing in Women's Educational Outcomes: An Examination of Educational Enrollment and Terrorism in Africa. Issue 2 (4th March 2023) - Danzell, Orlandrew E.; Yeh, Yao-Yuan; Sackeyfio, Naaborle
Abstract: This research examines the nexus between educational opportunities and incidences of domestic terrorism. Focusing on 50 African countries over the period 1970–2018, this article provides several novel contributions to the discourse. First, the article finds that differences in educational enrollment between women and men is likely to exacerbate domestic terrorism. This outcome is especially dire for women than that anticipated by well-meaning policymakers. Second, this article juxtaposes recent narratives which posit that increasing educational opportunities presents favorable outcomes. Instead, our article illustrates that the positive derivatives from a more equitable female-to-male educational enrollment is conditional. In particular, in some African countries where there is inadequate or an absence of consistent structures such as socioeconomic and labor market opportunities post–educational attainment, the intended positive consequences of education is often unrealized. Saliently, the relationship between increases in women's education and poor economic opportunities is likely to contribute to grievance-based domestic political violence.